2022
DOI: 10.3389/fonc.2022.739976
|View full text |Cite
|
Sign up to set email alerts
|

Tim-3 Blockade Elicits Potent Anti-Multiple Myeloma Immunity of Natural Killer Cells

Abstract: Multiple myeloma (MM) is still an incurable plasma cell tumor. Natural killer (NK) cells are characterized by efficient anti-tumor activity, and their activity is one basis of cancer immunotherapeutic strategies. Tim-3, one of the immune checkpoint molecules, negatively regulates NK cell activity. To evaluate roles of the Tim-3 pathway blocking in the regulation of NK cell mediated- anti-MM activity in vitro and in vivo, anti-Tim-3 and/or anti-its ligand (HMGB1, CEACAM1 or Galetin-9) antibodies were applied re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 32 publications
3
22
0
Order By: Relevance
“…We revealed that the activating receptor NKG2D expression increased, whereas the inhibitory receptor Tim-3 expression decreased. As shown in our previous studies, Tim-3 blockers could increase the killing function of NK cells on MM cells [30]. Coincidently, IFN-γ and TNF-α secretion was increased after TWS119 treatment.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…We revealed that the activating receptor NKG2D expression increased, whereas the inhibitory receptor Tim-3 expression decreased. As shown in our previous studies, Tim-3 blockers could increase the killing function of NK cells on MM cells [30]. Coincidently, IFN-γ and TNF-α secretion was increased after TWS119 treatment.…”
Section: Discussionsupporting
confidence: 74%
“…Our study signi cantly increased the cellular cytotoxic effect of NK-92 and primary NK cells, might provide reference signi cance for the allogeneic NK-92 cell transplantation and increase autologous NK cell antineoplastic function. In our previously study, we likewise showed that PD-1 and Tim-3 blockers increased cytotoxicity of NK cells against MM cells [20,30]. It might suggest that GSK-3β inhibitor combined with PD-1 and/or Tim-3 blockers may further enhance the cytotoxic activity of NK cells, which might support more potential immunotherapy approaches for other cancers.…”
Section: Discussionmentioning
confidence: 54%
“…A phase II clinical trial (NCT04847466) combining PD-L1 CAR-NK cells with pembrolizumab and N-803 is currently being studied in gastric and head and neck cancer. Similar to NKG2A, NK cell ex vivo expansion upregulates the expression of other exhaustion receptors, such as T cell Ig and mucin-containing domain-3 (TIM-3) ( 200 ) and T cell immunoreceptor with Ig and ITIM domains (TIGIT) ( 197 ). There is controversy regarding the role of TIM-3 in NK cell activity.…”
Section: Tumor Microenvironment: the Stumbling Block That Limits Car-...mentioning
confidence: 99%
“…Furthermore, NEK2 expression also upregulated AKT and Wnt (canonical) cascade. Interestingly, NEK knockdown by shRNA [1] , [2] , [3] , [4] was seen in ARP1 cells which increased the sensitivity to bortezomib with shRNA-3 being the most potent.…”
Section: Molecular Aspects Of MMmentioning
confidence: 99%
“…Emerging technological advancements in immunotherapy have expanded the scope of treatment modalities. Several checkpoint blockade therapies have been tested in patients including by targeting TIGIT [2] , LAG3/GAL-3 [3] , Tim-3 [4] and PD-L1 [5] . Interestingly, differential outcomes of MM patients treated with bortezomib-based therapies were associated with CTLA-4 polymorphisms [6] .…”
Section: Introductionmentioning
confidence: 99%